2013
DOI: 10.1542/peds.2012-0958
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Web-Based Application to Monitor Health-Related Quality of Life

Abstract: Our web-based application to systemically monitor HRQoL problems in pediatric rheumatology contributed significantly to communication about psychosocial issues in a positive way. We recommend implementation of ePROs in pediatric clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
165
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(170 citation statements)
references
References 38 publications
2
165
0
3
Order By: Relevance
“…20,21 KLIK utilization procedures were developed on the basis of many years of experience using PROs in diverse clinical contexts. 21,22 Several days before a scheduled appointment, the KLIK Web site generates an automatic e-mail that invites children aged 8 to 18 years or parents of children aged 0 to 7 years to complete electronic PRO (ePRO) measures through a secure Web site.…”
Section: Klik Eprofile: Emma Children's Hospital and Sint Lucas Andrementioning
confidence: 99%
See 4 more Smart Citations
“…20,21 KLIK utilization procedures were developed on the basis of many years of experience using PROs in diverse clinical contexts. 21,22 Several days before a scheduled appointment, the KLIK Web site generates an automatic e-mail that invites children aged 8 to 18 years or parents of children aged 0 to 7 years to complete electronic PRO (ePRO) measures through a secure Web site.…”
Section: Klik Eprofile: Emma Children's Hospital and Sint Lucas Andrementioning
confidence: 99%
“…This study demonstrated that physician access to the ePROfile led to more frequent discussions about children's emotional health and social functioning and greater physician satisfaction with the care they provided, particularly their capacity to provide emotional support. 20 Given its positive impact, the KLIK/ePROfile is now implemented in routine clinical care throughout Emma Children's Hospital and Sint Lucas Andreas Hospital. 20 …”
Section: Klik Eprofile: Emma Children's Hospital and Sint Lucas Andrementioning
confidence: 99%
See 3 more Smart Citations